Urban rural differences in diet, physical activity and obesity in India: are we witnessing the great Indian equalisation? Results from a cross-sectional STEPS survey - Jaya Prasad Tripathy; J. S. Thakur; Gursimer Jeet; Sohan Chawla; Sanjay Jain; Rajender Prasad (BMC, 2016)
Abstract Background The rising morbidity and mortality due to non-communicable diseases can be partly attributed to the urbanized lifestyle leading to unhealthy dietary practices and increasing physical levels of inactivity. The demographic and nutrition transition in India has also contributed to the emerging epidemic of non-communicable diseases in this country. In this context, there is limited information in India on dietary patterns, levels of physical activity and obesity. The aim of the present study was thus to assess the urban rural differences in dietary habits, physical activity and obesity in India. Methods A household survey was done in the state of Punjab, India in a multistage stratified sample of 5127 individuals using the WHO STEPS questionnaire. Results No rural urban difference was found in dietary practices and prevalence of overweight and obesity except the fact that a significantly higher proportion of respondents belonging to rural area (15.6 %) always/often add salt before/when eating as compared to urban area (9.1 %). Overall 95.8 % (94.6-97.0) of participants took less than 5 servings of fruits and/or vegetables on average per day. No significant urban rural difference was noted in both sexes in all three domains of physical activity such as work, transport and recreation. However, rural females (19.1 %) were found to be engaged in vigorous activity more than the urban females (6.3 %). Males reported high levels of physical activity in both the settings. Absence of recreational activity was reported by more than 95 % of the subjects. Higher prevalence of obesity (asian cut offs used) was seen among urban females (34.3 %) as compared to their rural counterparts (23.2 %). Abdominal obesity was found to be significantly higher among females in both the settings compared to males (p < 0.001). Conclusions Poor dietary practices and physical inactivity seems to fuel the non-communicable disease epidemic in India. Non communicable disease control strategy need to address these issues with a gender equity lens. Rapid urbanization of rural India might be responsible for the absence of a significant urban rural difference.